Malaysian and Indonesian Law and Policy on Rohingya Refugees: A Comparative Review - Siti Munirah Yusoff; Mohd Afandi Salleh; Md Mahbubul Haque (Universitas Muhammadiyah Yogyakarta, 2022)
Majority of ASEAN member countries consider themselves to be non-immigrant countries. As a result, the majority of ASEAN countries are not perfect locations for immigrants to settle. However, all states are bound by the non-refoulment principle laid down under Customary International Law in which, the states are prohibited to return the refugee to their original country where there was danger known around them. Hence, in the absence of a formal mechanism produce by the ASEAN region for the protection of refugees, Malaysia and Indonesia perform their efforts and experiences in terms of handling refugees. The paper explains the comparison of how the policy and law on refugees within Malaysia and Indonesia by referring to the case study on the Rohingya people crisis and also the Vietnamese boat people. The qualitative method has been chosen to explain the literature of the paper. This paper also discusses on how both countries respond to the right of a refugee within their sovereignty since they are non-signatory states to the 1951 Refugee Convention. As a result, the paper intends to elaborate on to what extent the laws and policies apply to the refugee according to the Malaysia and Indonesia experiences.